Fabrication of ZnO and TiO2 Combined Activated Carbon Nanocomposite and Adsorption Enhanced Synergetic Photocatalytic Effects - Zhu, Lei; Jo, Sun-Bok; Ye, Shu; Ullah, Kefayat; Oh, Won-Chun (Asian Journal of Chemistry, 2014)
The ZnO-AC/TiO2 compounds performance as photocatalyst have been investigated. The samples were checked by scanning electron microscopy, specific surface area, X-ray diffraction analysis and energy dispersive X-ray spectroscopy (EDX). The photocatalytic activities were evaluated by the photocatalytic oxidation of methylene orange solution. It was found that the prepared ZnO-AC/TiO2 composite material having excellent photocatalytic activity under visible light irradiation. A small amount of ZnO in composites AC/TiO2 significantly increase its photocatalytic activity.